Exploring Organisational Culture within a Radiology Department in NHS Setting - Shah, Jagrit (2012)
Organisational culture has received much attention in the last two decades due to its effects and potential impact on organisational success. Organisational culture affects employee behaviour which eventually affects the organisational performance. However, organisational theory and research suggest that culture is not homogeneous, but often fragmented in number of different subcultures in larger organisations. These subcultures could create internal tensions within the organisation, and have negative impact on performance. This study explores the organisational culture at two sites of the Radiology department of a large hospital trust in Nottingham which merged in 2006. Although, the merger occurred over 5 years ago, the two sites of the same department function as separate entities with very little cross-cover or transfer of knowledge. The hypothesis is that the subcultures within the department may be responsible for some of the recent safety incidents and suboptimal performance. The current consensus is that management interventions to improve organisational culture can improve performance. The study aim was to measure and compare the organisational culture at the two sites within the Radiology department, identify differences and similarities between the two sites with specific focus on culture deficits with view to recommending changes to improve the culture. A culture audit was carried out using a combination of questionnaire, targeted semi-structured interviews and observation of the departments. Based on literature and prior understanding of the issues in the department, 11 facets of organisational culture were interrogated. This study identified remarkable similarity in the organisational culture between the two sites despite of the differences in location, layout and procedures. Identical Organisational culture deficits in many of the facets of culture were identified across the two sites, with worse deficits in Performance Orientation, Communication Orientation and Management Orientation. Presence of subcultures within the department was also identified with different perceptions of culture amongst different groups in the department. Culture perception in the Consultants and Porters subgroup was worse than other groups. There is also a gender difference in perception of culture with perception of males worse than females. Any culture change intervention may therefore have to be targeted to the relevant groups and subcultures. Based on the study findings, recommendations are made to improve the culture in facets where deficits were identified. Successful implementation of these recommendations should improve the perception of organisational culture with happier, empowered and more engaged staff leading to a more sustainable change and better long term efficiency, safety, quality and outcomes.